Experimental and computational studies of the interactions between carbon nanotubes and ionic liquids used for detection of acetaminophen - Salvador, Michele A. (2019)
The interactions between multi-walled carbon nanotubes and different amounts of an ionic liquid (IL), as well asthe interactions between this system (used as electrochemical sensor) and acetaminophen (ACOP), were in-vestigated through both experimental and theoretical methodologies. Experiments indicated that there is anoptimal concentration of ionic liquid for ACOP detection. A host of techniques and model systems were em-ployed to investigate the adsorption and oxidation processes. To investigate the source of the increased elec-trochemical current in the presence of an IL, we computed the adsorption energy values of ACOP in the nanotube–IL system via Monte Carlo simulations and Density Functional Theory (DFT). DFT allowed us to explore thechanges in adsorption energy due to oxidation. Our theoretical results support the experimentalfindings thatmoderate amounts of IL modulates ACOP/ACOP+adsorption, pointing to a cooperative effect that tends to wanewith increasing amounts of IL pairs. We observed that the IL favors desorption of the oxidized species andfacilitates charge transfer from the ACOP to the nanotube. Therefore, our studies point towards multifactorialeffects with clear physical basis that modulates binding leading to an optimal ratio to promote ACOP detection